Relationship Between Sleep Quality and Blood Pressure Status in Undergraduate Nursing Students - Nabila Zahrian Puteri; Fahrun Nur Rosyid (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hypertension is a noncommunicable disease (NCD) that is a major cause of global mortality with a significant prevalence. Poor sleep quality, commonly experienced by students due to academic stress, contributes to hypertension. The purpose of this study is to analyze the relationship between sleep quality and blood pressure status in undergraduate nursing students. The research design was prospective, longitudinal study included 207 undergraduate nursing students in their third, fifth, and seventh semesters at Muhammadiyah University of Surakarta, selected through stratified random sampling. Data were collected in two phases (September - November) using the Pittsburgh Sleep Quality Index (PSQI) questionnaire which had been tested for validity and reliability (Cronbach’s Alpha > 0.70) and a digital sphygmomanometer. Analysis used the Generalized Estimating Equation (GEE) with α=0.05. The results showed that most students experienced poor sleep quality in stage 1 (71%) with (45.4%) experiencing prehypertension and in stage 2 (70%) with (51.7%) experiencing prehypertension. There was a significant relationship between sleep quality and blood pressure (Wald x² = 75.72; p < 0.001) with a B coefficient value of -2.185, which resulted in an odds ratio (OR) of 0.113. This indicates that respondents with poor sleep quality were 8 to 9 times more likely to experience higher blood pressure compared to those with good sleep quality. This study proves that poor sleep quality can increase the risk of hypertension in college students.